Diallyl Trisulfide Enhances the Survival of Multiterritory Perforator Skin Flaps - Dong, Chengji; Chen, Zhuliu; Zhu, Linxin; Bsoul, Najeeb; Wu, Hongqiang; Jiang, Jingtao; Chen, Xuankuai; Lai, Yingying; Yu, Gaoxiang; Gu, Yanlan; Guo, Xiaoshan; Gao, Weiyang (Frontiers in Pharmacology, 2022)
The multiterritory perforator flap is one of the widest flap patterns used to repair tissue defects. However, flap necrosis of the distal part is still a challenging issue for plastic surgeons. Diallyl trisulfide (DATS) is an efficient ingredient extracted from garlic, exerting many important effects on different diseases. Our experiment aims to reveal whether DATS has a beneficial effect on the survival of perforator flaps and to explore its mechanism of action. The results showed that DATS enhanced angiogenesis and autophagy and reduced cell apoptosis and oxidative stress, thereby improving the survival rate of skin flaps. After co-administration with autophagy inhibitor 3-methyladenine (3MA), perforator flap survival was further improved. Mechanistically, we showed that PI3K/Akt and AMPK-HIF-1α signaling pathways in flap were activated under DATS treatment. All in all, DATS promoted the survival of multiterritory perforator flaps via the synergistic regulation of PI3K/Akt and AMPK-HIF-1α signaling pathways, and inhibition of DATS-induced autophagy further improves flap survival.